Dual responsive polymeric nanoparticles prepared by direct functionalization of polylactic acid-based polymers via graft-from ring opening metathesis polymerization. Issue 3 (6th November 2015) - Veccharelli, Kate M.; Tong, Venus K.; Young, Jennifer L.; Yang, Jerry; Gianneschi, Nathan C.
Abstract : Graft-from polymerization enables generation of PLA-based materials with a high degree of incorporation of functional groups. Abstract : Polylactic acid (PLA) has found widespread use in plastics and in biomedical applications due to its biodegradability into natural benign products. However, PLA-based materials remain limited in usefulness due to difficulty of incorporating functional groups into the polymer backbone. In this paper, we report a strategy for PLA functionalization that establishes the preparation of highly derivatized materials in which ring opening metathesis polymerization (ROMP) is employed as a graft-from polymerization technique utilizing a norbornene-modified handle incorporated into the PLA backbone. As a demonstration of this new synthetic methodology, a PLA-derived nanoparticle bearing imidazole units protected with a photolabile group was prepared. The morphology of this material could be controllably altered in response to exposure of UV light or acidic pH as a stimulus. We anticipate that this graft-from approach to derivatization of PLA could find broad use in the development of modified, biodegradable PLA-based materials.